Dual-Mode, Dual-Polarization Fully-Woven Textile Antenna for Simultaneous Wireless Information and Power Transfer Applications in the 2.4 GHz Band - Miguel Fernandez; Carlos Vazquez; Samuel Ver Hoeye (IEEE Open Journal of Antennas and Propagation)
In this work, a dual-mode, dual-polarization fully-woven textile antenna for simultaneous wireless information and power transfer in the 2.4 GHz band is presented. It is based on a square patch with two independent ports. The first port is implemented with an offset T-match structure, to which a singlediode rectifier is connected. The selected feeding technique allows to obtain complex-conjugate impedance matching with the rectifier and right-hand circular polarization for the wireless power transfer mode. On the other hand, for the information transfer mode, a coaxial probe is used to excite the antenna with left-hand circular polarization, in order to minimize the coupling between both modes. The combination of fully-woven technology with the implementation of the rectifier on a carrier thread provides a high degree of integration and robustness. A prototype was implemented and experimentally characterized, showing good agreement with simulation results. Furthermore, the measured RF-DC conversion efficiency in the wireless power transfer mode is about 50% when the available power at the rectifier input is -10 dBm, which is comparable with the state of the art for textile rectennas.